Implementation of Literacy-Based Early Childhood Learning Program Management - Aprida, Siti Nurul; Muastiwi, Erni Munastiwi; Rahayu, Siti Sri (Aulad: Journal on Early Childhood, 2022)
The gersamasapa program is a literacy-based educational innovation created by At-Tauhid PAUD with the aim of increasing children's interest in reading and cultivating positive character in children. This study aimed to describe the implementation of literacy-based early childhood learning program management. The method used in this research is descriptive qualitative. Data collection techniques were using observation, interviews and documentation. There were nine subjects or informants in this study consisting of teachers and educational staff at At-Tawhid PAUD. The data collection process was carried out from November to December. The results of this study indicate that the process of 1) planning is carried out by holding a work meeting before the school year begins. The results of the meeting are then listed in the academic calendar and have standard operating procedures (SOP). 2) Organizing involves all parties by forming a gersamasapa program implementation team consisting of persons in charge, chairmen, members, and others which are then listed in an SK (decree). 3) The implementation of the gersamasapa program is carried out through three activities, including one house, one reading corner, literacy training, and storytelling classes. 4) Supervision is carried out by means of home visits and ABC monitoring books